Spectacular flares of the radio galaxy NGC 1275 measured with MAGIC - Dorit Glawion; Cosimo Nigro; Konstantin Pfrang; Pierre Colin; Vandad Fallah Ramazani; Daniel Mazin; Konstancja Satalecka (Italy, 2022)
We report on the detection of flaring activity from the prominent Fanaroff-Riley I radio galaxy NGC 1275 located in the Perseus cluster of galaxies in the very-high-energy gamma-ray band. The observations were performed with the MAGIC telescopes between 2016 and 2017 over several months. During this time period, the mean flux above 100 GeV was measured to be roughly ten times brighter than during previous observations. The night-by-night light curve above 100 GeV shows several peaks indicating flux-doubling time-scales of shorter than one day much smaller than the monthly time-scale previously detected by MAGIC. The brightest flux, observed around December 2016 and January 2017, reached 1.75 times the flux from the Crab Nebula, i.e. was about sixty times brighter than the average flux of the previous years. The spectral energy distribution measured up to > 1 TeV shows a curved shape unlike the previously measured simple power-law. The angle between the jet-axis and the line-of sight of NGC 1275 was formerly found to be 30-55 degree in the radio band excluding strong Doppler boosting of the emitted radiation towards the observer. The fast TeV flux variability and the spectral behaviour observed from a non-blazar object challenge current standard theoretical models and therefore, provide new and fascinating insights into the gamma-ray production and emission mechanism of active galactic nuclei. In the conference, we present the observational results and discuss possible physical processes responsible for the flaring events.
35th International Cosmic Ray Conference, ICRC 2017